The Green Islam Movement in Indonesia: Actors, Strategies, and Networks - Testriono, Testriono; Ropi, Ismatu; Auliya, Aldi Nur Fadil; Ibmar, Dedy; Billahi, Savran; Rohayati, Tati (Studia Islamika, 2025)
The Center for the Study of Islam and Society (PPIM), Syarif Hidayatullah State Islamic University (UIN) Jakarta conducted a study entitled Gerakan Green Islam di Indonesia: Aktor, Strategi, dan Jaringan (The Green Islam Movement in Indonesia: Actors, Strategies, and Networks). This study seeks to answer why and how the Green Islam movement has developed in Indonesia, who their key actors are and how they build their networks, and how Green Islam activists use religious identity to design their strategies and programs.This qualitative research, carried out over eight months, employed a case study approach and utilized data collection techniques including desk research (November 2023–January 2024), focus group discussions (FGDs; February–March 2024), in-depth interviews (April–May 2024), and observations (April–May 2024). FGDs were conducted in Jakarta and Surabaya, involving 50 leaders of faith-based environmental organizations or communities. In addition, the research conducted in-depth interviews with 53 informants from Green Islam organizations or communities and carried out observations in 28 environmental work sites belonging to 10 Green Islam organizations or communities across Indonesia.